Leprosy among new child cases in China: Epidemiological and clinical analysis from 2011 to 2020. - Jiayi Peng; Peiwen Sun; Le Wang; Hongsheng Wang; Siyu Long; Mei-Wen Yu (Public Library of Science (PLoS), 2023)
Background Leprosy, caused by Mycobacterium leprae infection, mainly affects skin and peripheral nerves and may further lead to disability and deformity if not treated timely. The new case detection rate of leprosy in children reflects the active transmission of leprosy infection. This study aims to present the epidemiology and clinical characteristics of new leprosy cases in children in China from 2011 to 2020. Methodology/principal findings All data from leprosy patients younger than 15 years old were extracted from the Leprosy Management Information System in China (LEPMIS). Statistical Package for the Social Sciences (SPSS) version 12.0 was used for descriptive and analytical statistics of the epidemiological and clinical indicators by the Mann-Whitney test, Kruskal-Wallis test, and Fisher's exact test. And geographical distribution was analyzed by ArcGIS 10.5. A total of 152 pediatric new cases of leprosy were found over the last decade. The new case detection rate of pediatric leprosy cases decreased from 0.13 to 0.02 per 1,000,000 population over the last ten years. New pediatric cases had a higher new case detection rate in Guizhou, Sichuan, and Yunnan Provinces. All but 7 provinces in China achieved zero new child case for consecutive five years. The onset of leprosy peaked between 10 and 14 years of age, and the male to female ratio was 1.71:1. Pediatric patients were predominantly infected from symptomatic household adult contacts HHCs. Multibacillary leprosy (MB) was the most common. However, a low proportion of patients developed leprosy reaction and grade 2 disability. Conclusions/significance The new case detection rate of pediatric leprosy cases has decreased over the past ten years in China. Spatial analysis indicated clusters in high-endemic areas. Leprosy transmission has stopped in the majority of provinces in China. However, sporadic cases may continue to exist for a long time. Active surveillance especially contact tracing should be focused on in future plan for management of leprosy, and interventions in leprosy clusters should be prioritized.